Bruxismo e tipo de respiração como fatores associados ao auto-relato de lesão por herpes oral em para-atletas brasileiros - Costa, Eugênio Esteves (2020)
The main goal of the present study investigated the factors, among them bruxism and type of breathing, involved in recurrent manifestation of oral herpes lesions in paraathletes. The studied population was composed of a convenience sample of 370 Brazilian para-athletes. All included individuals answered questionnaires and were submitted to an oral examination. A self-reported questionnaire addressed demographic and oral health data, including manifestation of oral herpes lesions. The Oral Health Impact Profile was also applied in its reduced version with 14 questions. The population was categorized according to results from previous competitions into high performance level, medium performance level, and regional performance level. Chi-square or Fisher´s exact tests, Odds Ratio calculation, and t tests were performed ( =5%). Sixty (16.2%) para-athletes reported recurrent manifestation of oral herpes lesions. Paraathletes with sleep (OR=2.25, CI95% 1.23-4.12; p=0.007) and awake (OR=1.68; CI95% 1.00-2.98; p=0.048) bruxism had a higher chance of reporting oral herpes lesions. Type of breathing was also associated with oral herpes lesions (p=0.02). The Oral Health Impact Profile questionnaire distribution among the groups was not statistically significant (p>0.05). In conclusion, bruxism and type of breathing were associated with self-reported oral herpes lesions in Brazilian para-athletes.